2012
DOI: 10.1007/s00396-012-2677-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nonspherical particles via dual-seeded dispersion polymerization in the presence of saturated hydrocarbon droplets

Abstract: In this study, the effect of various polymerization conditions on the shape of the particles produced by dualseeded dispersion polymerization of a second monomer with polystyrene (PS) and poly(methyl methacrylate) (PMMA) seed particles in the presence of saturated hydrocarbon droplets in a polar media was discussed. It was observed that with changing the affinity between the hydrocarbon and PS seed particles, second monomer type, polarity, and alcohol type of the medium nonspherical particles with a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Such observations are very important due to different functionalities each one of the mentioned shapes have. In our previous work, we reported the production of novel and unique almond-shelllike PS particles via DSDP technique, but formation mechanism of them remained unclear even though the obtained results helped us to introduce a hypothetical one [24]. Therefore, in order to illustrate this point clearly as well as achieving exceptional results that was referred to above, we tried monitoring the DSDP system.…”
Section: Time Course Analysis Of Dsdpmentioning
confidence: 78%
See 2 more Smart Citations
“…Such observations are very important due to different functionalities each one of the mentioned shapes have. In our previous work, we reported the production of novel and unique almond-shelllike PS particles via DSDP technique, but formation mechanism of them remained unclear even though the obtained results helped us to introduce a hypothetical one [24]. Therefore, in order to illustrate this point clearly as well as achieving exceptional results that was referred to above, we tried monitoring the DSDP system.…”
Section: Time Course Analysis Of Dsdpmentioning
confidence: 78%
“…2. One of the challenges in the DSDP system is to characterize each one of the seed particles apart from each other during microscopic tests; however, in this type of DSDP, it is not so hard to do so since it was found in previous studies that PMMA seed particles coagulate during polymerization [23,24]. Nevertheless, monitoring the reaction was expected to be an excellent way to determine the time when this phenomenon happens.…”
Section: Time Course Analysis Of Dsdpmentioning
confidence: 96%
See 1 more Smart Citation
“…In the past years, several efforts have been done to prepare such particles using different techniques [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. We also reported the production of particles with a variety of shapes [19][20][21][22][23][24]. However, in all of such reports, nonspherical particles have been produced by changing the shape of a precursor; therefore, this question would be raised: Bis it feasible to prepare nonspherical particles of one component directly by polymerization without changing the shape of a precursor?Î n our previous work, we answered this question by introducing a new synthesis method which we called it micromolding-polymerization.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have been reported regarding the production of polymer particles with a variety of shapes such as "egg-like" [1], "confetti-like" [2], "raspberry-like" [3][4][5][6], "snowman-like" [2,7], "rugby-ball-like" [8], golf-ball-like [9], disk-like [10][11][12][13], red blood corpuscle-like [14], and so forth. We have also reported the fabrication of particles with novel almond shell-like shape via dual-seeded dispersion polymerization (SDP) [15,16] as well as half-shell polystyrene (PS) particles with controllable surface area using micromolding-polymerization [17].…”
Section: Introductionmentioning
confidence: 98%